Treatment of the Bullet, Traversing Femoral Neck, Lodged in Hip Joint: Initial Arthroscopic Removal and Subsequent Cartilage Repair - Çatma, Mehmet Faruk (J Orthop Case Rep, 2016)
INTRODUCTION: There have been several reports on arthroscopically assisted removal of the bullet imbedded in hip joint in the literature. Similarly, in this case, a bullet lodged in acetabulum was extracted with arthroscopic technique. What makes this case unique in the literature is that the bullet removed from the acetabulum traversed the femoral neck. CASE REPORT: Male patient aged 32 years with a low-velocity gunshot wound was referred to the emergency room on August 28, 2012. The projectile was lodged in acetabular side of the hip joint transversing through the femoral neck. A hip arthroscopy was performed for bullet removal. Two years after surgery, the patient had groin pain and underwent a safe dislocation for femoral chondral injury. In the last follow-up in the second post-operative year, the patient had no clinical complaint. CONCLUSION: Hip arthroscopy is a minimally invasive and proper procedure for removal of foreign materials such as a bullet in the hip joint. Arthrotomy can be reserved for further complications such as chondral injury as in this case.